A coupled 3D wear and fatigue numerical procedure: Application to fretting problems in ultra-high strength steel wires. (February 2021) - Llavori, I.; Zabala, A.; Mendiguren, J.; Gómez, X.
Highlights: An improved coupled 3D fretting wear and fatigue numerical procedure is proposed. Crack initiation locations were predicted accurately. The contact stiffness is a key factor in replicating the contact behavior during wear process. A novel damage interpolation scheme, coined as CCPM, is proposed. Abstract: This work presents a coupled 3D wear and fatigue numerical procedure for fretting problems in ultra-high strength steel wires that combines Archard's wear equation with the Smith–Watson–Topper parameter to predict crack nucleation. For total life prediction, a mode I crack propagation based on the weight function method was used. To assess fretting fatigue lifetime, several experimental campaigns were run. The numerical results were in good agreement with the fretting fatigue experimental results. Thus, this study provides a 3D numerical methodology to study the combined effects of wear and fatigue in fretting with a case study in ultra-high strength steel wires.